Incidence and Characteristic of Psoriasis Patients at Sanjiwani Gianyar Regional Hospital 2018-2019 - Annisa Alviariza; Sayu Widiawati (Majalah Kesehatan Indonesia, 2021)
Psoriasis is a chronic inflammatory skin disease that is characterized by firmly demarcated red plaque covered by a thick squama as a result of impaired proliferation and differentiation of the epidermis. Diagnosis of psoriasis is based on history taking and clinical features. Treatment is determined based on the patient's clinical characteristics and the severity of the disease. this retrospective study aims to determine the incidence, characteristics and treatment options of psoriasis patients in the dermatovenereology polyclinic of Sanjiwani Gianyar Regional Hospital in 2018-2019. Retrospective study of psoriasis patients at Sanjiwani Gianyar Regional Hospital in 2018-2019. Data collected from medical records includes sociodemographic data, clinical data and patient treatment history. Within two years, there were 53 new cases of psoriasis. The dominance of psoriasis cases was found in men with a ratio of women and men 1:2,31. From total 53 patients, 37 were male (69,81%)and 16 female patients (30,19%). The most common type was psoriasis Vulgaris (73,58%). The most age group was 31-45 years. The most commonly given regimen of therapy was topical corticosteroids plus oral antihistamines (45,28%). The most widely given systemic therapy was methotrexate. Accompanying skin infections were found in 6 cases of psoriasis (11,32%). Based on the results of the study, there were 53 new cases of psoriasis in 2018-2019, psoriasis Vulgaris was the most common, the most age group was 31-45 years old, topical corticosteroids plus antihistamines were still the main treatment options for psoriasis patients in Sanjiwani Gianyar Regional Hospital.  Abstrak: Psoriasis adalah penyakit kulit inflamasi kronis yang ditandai dengan plak merah berbatas tegas tertutup skuama tebal sebagai akibat dari gangguan proliferasi dan diferensiasi epidermis. Diagnosis psoriasis dilakukan berdasarkan anamnesis dan gambaran klinis. Terapi ditentukan berdasarkan karakteristik klinis pasien dan derajat keparahan penyakit. Penelitian retrospektif ini bertujuan untuk mengetahui insiden, karakteristik dan pilihan terapi pasien psoriasis pada Poliklinik Kulit dan Kulit Kelamin RSUD Sanjiwani Gianyar pada tahun 2018-2019. Studi retrospektif selama 2 tahun pada pasien psoriasis di Poliklinik RSUD Sanjiwani Gianyar pada tahun 2018-2019. Data dikumpulkan dari rekam medis mencakup data sosiodemografik, data klinis, serta riwayat pengobatan pasien. Dalam dua tahun terdapat 53 kasus baru psoriasis. Dominasi kasus psoriasis ditemukan pada laki-laki dengan rasio perempuan dan laki-laki 1:2,31. Dari total 53 pasien didapatkan 37 pasien laki-laki (69,81%) dan 16 pasien perempuan (30,19%). Jenis yang paling banyak adalah psoriasis vulgaris (73,58%). Kelompok usia yang paling banyak adalah 31-45 tahun. Regimen terapi yang paling sering diberikan adalah kortikosteroid topikal ditambah antihistamin oral (45,28%). Terapi sistemik yang paling banyak diberikan adalah metotrexate (43,40%). Infeksi kulit penyerta terdapat pada 6 kasus psoriasis (11,32%). Berdasarkan hasil penelitian, didapatkan insiden kasus psoriasis tahun 2018-2019 sebanyak 53 kasus, dengan kasus terbanyak psoriasis vulgaris, kelompok usia terbanyak adalah usia 31-45 tahun, kortikosteroid topikal ditambah antihistamin masih merupakan pilihan terapi utama untuk psoriasis di RSUD Sanjiwani Gianyar.